Assessment of Bendopnea and Its Association With Clinical and Para‐Clinical Findings in Systolic Heart Failure: A Cross‐Sectional Study - Elmira Javanmardi; Tara Reshadmanesh; Sepehr Gohari; Amir Hossein Behnoush; Hassan Ahangar (Health Science Reports)
ABSTRACT Background and Aims Bendopnea is a symptom found in patients with heart failure (HF) defined as shortness of breath when bending forward. The present study examined the correlation between bendopnea with other cardiac symptoms, echocardiographic findings, and cardiac function parameters. Methods This was a single‐center prospective cross‐sectional study of patients diagnosed with systolic HF. Medical history, bending tests, laboratory tests, electrocardiography (ECG), echocardiography, and 6‐min walking test (6‐MWT) were evaluated. Patients with reduced ejection fraction were followed to assess the 2‐year outcomes for cardiovascular death and rehospitalization. Results A total of 80 patients were included in this study, of whom 54 (67.5%) were male. Bendopnea was present in 34 (42.5%) and their mean age was 62.44 years (compared to group without bendopnea, p = 0.869). Symptoms of HF such as dyspnea of exertion (DOE) and orthopnea were significantly related to the presence of bendopnea (p = 0.001, odds ratio (OR): 6.87, and p = 0.016, OR: 3.18, respectively). The bendopnea‐positive group had a higher New York Heart Association (NYHA) class (p = 0.005). ECG results showed no significant difference between the two groups. The echocardiographic findings showed that the inferior vena cava (IVC) respiratory collapse was significantly lower in the bendopnea‐positive group (p = 0.019, OR: 0.339, 95% CI:0.13–0.85). Moreover, they had a substantially lower performance in 6‐MWT (387.39 vs. 325.58 m, p = 0.015). Neither rehospitalization nor death was related to bendopnea after a 2‐year follow‐up (p = 0.454). Conclusion Bendopnea was associated with several signs and symptoms of HF, including orthopnea, DOE, NYHA class, lower IVC collapse, and impaired functional capacity measured via 6‐MWT. However, there was no association between bendopnea and ECG findings, ejection fraction, and NT‐proBNP levels. Further studies with larger sample sizes are needed to assess the associations with long‐term outcomes and confirm our findings.